SHARIAH-COMPLIANT OF NURSING CHILD DOCUMENTATION MODEL BUILDING - Siti Fatimah Salleh ,Solehhuddin Bin Zakaria ,Lukman Abdul Mutalib ,Rogayah Saeed Salameh Alqaraleh ,Dhamirah Nursakinah Binti Mohamad Safir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Shariah-compliant nursing child documentation model was developed due to the variety of ways and forms of breastfeeding among Muslim communities in Malaysia. This article aims to explain the model of nursing child documentation based on the perspective of the Shariah maqasid in managing Shariah-compliant nursing child issues. The methodology used is qualitative research using case study design and obtaining research data through document analysis and interviews. Study found that the model conforms to the al-Khams dharuriyyat element which involves the preservation of religion and descent. The model also has the potential to be managed at the state religious office or nationally and internationally in resolving marital issues and a number of other social issues, in ensuring the well-being of families and family harmony.